TEŃEW HÁM EPITETLERDIŃ STILLIK QOLLANILIW ÓZGESHELIKLERI - Allanazarov, E.; Erniyazova, G. (SCIENCE and SOCIETY, 2023)
In article, one of the linguistic units of our language is devoted to the event of the use of phraseological units in an artistic language. In the works there are given concerning the peculiarities of the meaning of the word in use.
Keywords: linguistic; phraseological; language; kontekst; concerning; peculiarities; semantical; forma